INCIDENCE OF URETHRAL STRICTURE FOLLOWING BIPOLAR TRANSURETHRAL RESECTION OF PROSTATE - INAMULLAH, S; KHAN, F (Biological and Clinical Sciences Research Journal, 2024)
Benign prostatic hyperplasia (BPH) is a prevalent condition among older men, often treated with transurethral resection of the prostate (TURP). Bipolar TURP (B-TURP) has gained popularity due to its reduced risk of complications compared to monopolar TURP. However, postoperative urethral stricture remains a significant concern. Objective: This study aims to evaluate the incidence and risk factors associated with urethral stricture following B-TURP in a cohort of patients from a tertiary care center at the Urology Department, Lady Reading Hospital Peshawar KPK, Pakistan. Methods: This prospective study analyzed 136 patients who underwent B-TURP. Patient demographics, clinical parameters, perioperative details, and postoperative complications were recorded. Statistical analyses were performed to identify factors significantly associated with urethral stricture development. Results: The incidence of urethral stricture was 5.9%. A smaller metal caliber was significantly associated with stricture formation (mean caliber 25 Fr in patients with strictures vs. 28 Fr without; P = 0.001). Other factors such as prostate volume, diabetes mellitus, resectoscope sheath size, resection time, capsular perforation, and perioperative complications did not show a significant correlation with stricture development. Conclusion: Urethral stricture following B-TURP is relatively uncommon, with meatal caliber being an important predictor of risk. These findings align with recent literature, highlighting the importance of preoperative and perioperative factors in managing and mitigating the risk of strictures. Further, multi-center studies are needed to validate these results and explore additional preventive measures.